Growth, physiological and biochemical responses as affected by paclobutrazol for flowering induction on water induced stress mango plants (Mangifera indica L. cv. Harumanis) - Aris, Nur Afiqah (2015)
Harumanis is the most popular mango cultivar in Malaysia for local fresh market as well as for export. However, flowering of Harumanis seem to be influenced by weather changes. Thus, suitable weather condition is required for Harumanis to initiate flowering. Basically, mango plant needs a long dry period in order to produce reproductive sprouts. Hence, it is very crucial to understand the role of drought in initiating flowering. Flowering of Harumanis can also be induced chemically by using paclobutrazol, a plant growth regulator to enhance the yield. Therefore, this study was conducted to determine the effect of paclobutrazol and water stress on vegetative growth, physiological and biochemical responses, and flowering of Harumanis. The application of paclobutrazol (0.75g a.i./tree) on three-year old containerized mango (Mangifera indica cv. Harumanis) was investigated in the field during December 2011 until March 2012 in randomized design with seven replications. Three treatments were imposed onto the tree of which T1 as control tree and irrigated daily (soil water potential maintain at 0 to -15 kPa); T2: 0.75g a.i. of paclobutrazol was applied as soil drench followed by imposed stress for 21 days (soil water potential maintain at - 40kPa); and T3: Imposed stress for 30 days (soil water potential maintain at -40 kPa). T2 and T3 trees were irrigated after the dry period. Among the treatments, paclobutrazol with water stress (T2) significantly reduced shoot length and leaf development i.e. leaf size and leaf area compared to the other treatments. The physiological and biochemical content of mango plants were affected by paclobutrazol and water stress (T2) compared to control (T1) and stressed trees (T3). Paclobutrazol significantly reduced the photosynthesis rate, stomatal conductance and transpiration rate; but it increased sucrose and starch content in mango leaves. Moreover, the trees treated with paclobutrazol and water stress (T2) produced compacted flowers with short panicles and less number of fruit set. There was a few flowering occurred in the control trees (T1), while no flowering occurred in the water stressed trees (T3) up to 12 weeks of the experimental period (Appendix F1). The physiological response i.e. photosynthesis rate, stomatal conductance, and transpiration of paclobutrazol treated trees were higher during pre-floral stage and decreased during flower bud formation, but increased during flowering bloom. The biochemical content i.e. chlorophyll content, sucrose content, and starch concentration were higher during pre-floral stage compared to during flower initiation, flower bud and flower bloom. These results suggest that paclobutrazol and water stress could effectively enhance flowering of mango.